PENINGKATAN KETERAMPILAN BERMAIN PIANIKA MELALUI METODE TUTOR SEBAYA - Henny , Widyawati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
The researcher tries to solue the problem about the lark of students’ skill in playing ’pianica’ at SMPN 11 Tambun Selatan. The subject of the research are the 46 students of class IX.3, in 2015/2016 academic year. The research method used is an action research. The result shows that there is an improvement of the eagerness and the study result from cycle I and II. The passing grade for this study is 70 there are 13 students (28,20%) who get > 70. In cycle I, there is an improvement which is shown that there are 31 students (67,39%) who get > 40. Moreover, in cycle II, there is a significant improvement which is show that all students’ (100%) get > 70. The conclusion of the research is pear tutors method can improve the activity and the result of study playing ’pianica’, especially at SMPN 11 Tambun Selatan class IX.3.Keyword: skill, pianica, peer tutors.